Effects of interface conditions on heat and mass transfer during modeling of laser dissimilar welding. (February 2022) - Li, Zhiyong; Yu, Gang; He, Xiuli; Li, Shaoxia; Wang, Xu; Li, Zixun; Li, Haiming
An improved 3 D heat and mass transfer model was developed to study the effects of interface conditions during modelling of laser dissimilar welding. In detail, the interface conditions consist of the physical processes at gas/liquid surface (e.g. free surface deformation and optical absorptance), substrate interface (e.g. mixture properties in liquid phase and thermal contact condition) and solid/liquid interface (e.g. fusion line). Their effects on heat and mass transfer are numerically and experimentally analyzed, which are all non-negligible in the welding modelling. In conclusion, free surface deformation influences convection flow and should be considered in the situation of micro-welding and high energy-input welding. Besides, the energy transfer between laser and substrate is more reasonably described by the optical absorptance expressed in polynomial function. The mass transfer induced variation of mixture properties is well described by the method based on time-dependent mixture fraction. Thermal resistance between clamp and substrate should be considered in the modelling of temperature field on macroscale. The joint conductance at substrate interface could be neglected when modelling heat and mass transfer inside the melt pool, while it should be calculated in the simulation of temperature distribution based on the mechanism of heat conduction. The obtained results in this paper provide a vital insight into the interface conditions in laser dissimilar welding process.